Proceedings of the 2012 International Conference of Modern Computer Science and Applications - Du, Zhenyu; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
This volume contains the proceedings of the 2012 International Conference of Modern Computer Science and Applications (MCSA 2012) which was held on September 8, 2012 in Wuhan, China. The MCSA 2012 provides an excellent international forum for sharing knowledge and results in theory, methodology and applications of modern computer science and applications in theoretical and practical aspects.
Computational Methods, Algorithms and Scientific Applications -- Computer Networks -- Geometric Modeling, Graphics and Visualization Computer Networks -- Geometric Modeling, Graphics and Visualization -- Computer Science Applications in Education -- Computer Science Applications in Business and Social -- Modern and Emerging Applications.
Keywords: Engineering; Artificial intelligence; Engineering; Computational Intelligence; Artificial Intelligence (incl. Robotics).